Detectable depth of unexposed parathyroid glands using near-infrared autofluorescence imaging in thyroid surgery - Han, Young Seok; Kim, Yikeun; Lee, Hyoung Shin; Kim, Yeongjoon; Ahn, Yeh-Chan; Lee, Kang Dae (Frontiers in Endocrinology, 2023)
Background: Near-infrared light can penetrate the fat or connective tissues overlying the parathyroid gland (PG), enabling early localization of the PG by near-infrared autofluorescence (NIRAF) imaging. However, it has not been reported how deep the PGs can be detected. In this study, we investigated the detectable depth of the unexposed PG during thyroidectomy using NIRAF. Materials and Methods: Fifty-one unexposed PGs mapped by an experienced surgeon (K.D. Lee) with the use of NIRAF imaging from 30 consecutive thyroidectomy patients were included. For NIRAF detection of PGs, a lab-built camera imaging system was used. Detectable depths of the unexposed PGs were measured using a Vernier caliper. The brightness of the NIRAF intensity was classified into faint and bright groups depending on whether the novice could interpret it as PG. Data on variables that can affect the detectable depth and NIRAF intensity were collected. Results: The detectable depth ranged 0.35 - 3.05 mm with a mean of 1.23 ± 0.73 mm. The NIRAF intensity of the unexposed PGs averaged 3.13 au. After dissection of the overlying tissue, the intensity of the exposed PG increased to 4.88 au (p < 0.001). The NIRAF intensity between fat-covered (3.27 ± 0.90 au) and connective tissue-covered PGs (3.00 ± 1.23 au) showed no difference (p = 0.369). PGs buried by fat tissue (depth, 1.77 ± 0.67 mm) were found in deeper locations than connective tissue (depth, 0.70 ± 0.21 mm) (p < 0.001). The brightness of the faint group (2.14 ± 0.48 au) was on average 1.24 au lower than that of the bright group (3.38 ± 1.04 au)(p = 0.001). The novice localized 80.4% of the unexposed PGs. Other variables did not significantly affect the detectable depth. Conclusion: Unexposed PGs could be mapped using NIRAF imaging at a maximum depth of 3.05 mm and an average depth of 1.23 mm. The novice was able to localize the PGs before naked eye at a high rate. These results can be used as reference data to locate the unexposed PG in thyroid surgery.